Understanding the role of Leisure Involvement and Choice Complexity on Choice overload in booking of leisure activities online among Young Consumers - Rakesh Gandla, Aditi Saurav, Priyanka Sahoo; Vihang Golla, Lalith Kumar Vemali, Mechri Saravanan Pallavi (Journal of Informatics Education and Research, 2024)
People are faced with an oversupply of almost ever type of good. Due to the large number of options, it has become very important for service providers to understand, how customers act when they book leisure activities online. As far as the researcher knows, no one has looked into how having too many options affects people's decisions when they book leisure activities online before. This study looks at the difference between leisure activities done at home and while on holiday, taking into account the issue of choice overload when booking leisure activities online. There is a plan to use an integrated research approach that utilizes cognitive dissonance as well as spillover theories to testhypotheses. This study employed Gen Y (17-37 years) who have visited Goa in the last six months. The study's conclusions have consequences for both tourism-related businesses and consumers, guiding how they act, their emotions, judgments, and behaviors toward evaluating the alternatives.